Investigating the role of nasal muscles in nasal obstruction after open technique rhinoplasty: A case-control study by electromyographic evaluation - Seyed Resuli, Ali; Ataus, Sureyya (Journal of Surgery and Medicine, 2020)
Aim: Although the effects of rhinoplasty on nasal muscles by electromyography (EMG) or electroneuronography have been studied, the role of the nasal muscles in nasal obstruction after rhinoplasty operations has not yet been investigated. The aims of this study were to investigate the influence of the open rhinoplasty on nasal muscles and to reveal the role of the nasal muscles in post-operative nasal obstruction. Methods: Thirty-five patients who underwent open technique rhinoplasty by a single surgeon due to external nasal deformity were included in the study. The patients were divided into two groups six months after the surgery: Study group with nasal obstruction and control group without nasal obstruction. EMG was performed to all patients for the activity of M. procerus, M. transversus nasalis and M. dilator before and after rhinoplasty. Results: It was observed that the amplitudes of M. transversus nasalis and M. dilator muscles in the patients with nasal obstruction were significantly lower than the patients without nasal obstruction (P=0.01, P=0.003, respectively). Post-operative electromyographic activities of nasal muscles significantly decreased in all patients compared to pre-operative amplitudes. Conclusion: This study demonstrated that nasal muscles or SMAS may be damaged during open technique rhinoplasty and as a result of this damage (especially in M. transversus nasalis and M. dilator) nasal respiration can be affected, which may lead to post-operative nasal obstruction. Preservation of these muscles and SMAS during rhinoplasty operations may reduce the incidence of post-operative nasal obstruction.